Sexual satisfaction of women partners of circumcised men in a randomized trial of male circumcision in Rakai, Uganda - Kigozi, Godfrey; Lukabwe, Ivan; Kagaayi, Joseph; Wawer, Maria J.; Nantume, Betty; Kigozi, Grace; Nalugoda, Fred; Kiwanuka, Noah; Wabwire-Mangen, Fred; Serwadda, David; Ridzon, Renee; Buwembo, Dennis; et al. (AIDS (London, England), 2016)
To investigate the effect of adult medical male circumcision on female sexual satisfaction. We investigated self-reported sexual satisfaction among 455 women partners of men circumcised in a randomized trial of male circumcision for the prevention of human immunodeficiency virus in Rakai, Uganda. Women aged 15–49 years were interviewed about their sexual satisfaction before and after their partners were circumcised. We analyzed female-reported changes in sexual satisfaction using chi-square or Fisher’s exact tests.
Keywords: Sexual satisfaction; Male circumcision; women